2018
DOI: 10.29333/ejmste/89940
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Project Activity to Enhance the Scientific Process Skill and Self-Efficacy in Zoology of Vertebrate Teaching and Learning

Abstract: This study is a quantitative research conducted to analyze the integration of project activity to increase the scientific process skill and self-efficacy. While uncovering the effect of each indicator of every predictor, a descriptive qualitative analysis has been done. Respondents in this research were biology students in teacher. The sample of 30 respondents were taken by random sampling technique. Research instruments were in the form of scientific process skill test and self-efficacy inventory. The hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 36 publications
1
23
0
3
Order By: Relevance
“…The picture book that contains science made effective to learn and understand the concept of science (Beaumont, et al, 2017). On the other hand, Hernawati, et al (2018) showed that project activities were integration in learning and impacted in science process skill of student higher. One of the skills was observation skill, the scientific approach contributed to an increasing this skill, observational skill, in high quality .…”
Section: Resultsmentioning
confidence: 99%
“…The picture book that contains science made effective to learn and understand the concept of science (Beaumont, et al, 2017). On the other hand, Hernawati, et al (2018) showed that project activities were integration in learning and impacted in science process skill of student higher. One of the skills was observation skill, the scientific approach contributed to an increasing this skill, observational skill, in high quality .…”
Section: Resultsmentioning
confidence: 99%
“…The learning habit using the scientific approach could improve the students' ability both cooperatively and collaboratively. Therefore, the exploration through learning activities in observation, making inquiries related to observations, conducting experiments, reasoning and communicating results through various interpretations needed improvement (Hernawati et al, 2018). The accumulation of all these stages would improve the intellectual ability, especially in higher-order thinking skills.…”
Section: Resultsmentioning
confidence: 99%
“…In the self-efficacy blueprint, the statements are divided into three sections that fulfill three dimensions of self-efficacy: magnitude, strength, and generality [58]- [60]. The first is the aspect of magnitude regarding students' beliefs in terms of their ability to solve various levels of difficulty in reading assignments.…”
Section: Self-efficacy Scalementioning
confidence: 99%
“…The third is the generality aspect, which is the area of behavior, including the beliefs of students completing various variations of reading tasks. Indicators of this aspect are students' confidence that can solve various reading problems and confidence and have consistency in various situations [60].…”
Section: Self-efficacy Scalementioning
confidence: 99%